Testing the Translational Power of the Zebrafish: An Interspecies Analysis of Responses to Cardiovascular Drugs - Margiotta-Casaluci, Luigi; Owen, Stewart F.; Rand-Weaver, Mariann; Winter, Matthew J. (Frontiers in Pharmacology, 2019)
The zebrafish is rapidly emerging as a promising alternative in vivo model for the detection of drug-induced cardiovascular effects. Despite its increasing popularity, the ability of this model to inform the drug development process is often limited by the uncertainties around the quantitative relevance of zebrafish responses compared with non-clinical mammalian species and ultimately humans. Here we provide a comparative quantitative analysis of the in vivo cardiovascular responses of zebrafish, rat, dog, and human to three model compounds (propranolol, losartan, and captopril), which act as modulators of two key systems (beta-adrenergic and renin-angiotensin systems) involved in the regulation of cardiovascular functions. We used in vivo imaging techniques to generate novel experimental data of drug-mediated cardiovascular effects in zebrafish larvae. This data was combined with a database of inter-species mammalian responses (i.e. heart rate, blood flow, vessel diameter, stroke volume) extracted from the literature to perform a meta-analysis of effect size and direction across multiple species. In spite of the high heterogeneity of study design parameters, our analysis highlighted that zebrafish and human responses were largely comparable in >80% of drug/endpoint combinations. However, it also revealed a high intra-species variability which, in some cases, prevented a conclusive interpretation of the drug-induced effect. The meta-analysis approach, combined with a suitable data visualization strategy, enabled us to observe of patterns of response that would likely remain undetected with more traditional methods of qualitative comparative analysis. We propose that expanding this approach to larger datasets encompassing multiple drugs and modes-of-action, would enable a rigorous and systematic assessment of the applicability domain of the zebrafish from both a mechanistic and phenotypic standpoint. This will increase the confidence in its application for the early detection of adverse drug reactions in any major organ system.